Is there a Relationship Between Pregnant Women's Characteristics and Stunting Incidence In Indonesia? (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Teenage pregnancy has an impact on the outcomes. Teenage pregnancy is at risk of adverse health, an increased risk of domestic violence, poor nutrition, and sexual and reproductive health problems, lower levels of education, and higher levels of poverty compared to women who postpone marriage age. The study aims to determine the relationship between marriage and Adolescent pregnancy with the incidence of stunting in children under five years in Indoneasia.Â  The study used a cross-sectional approach from 2014 IFLS (Indonesian Family Life Survey) data. The bivariate analysis used the Chi-Square Test when the multivariate analysis used logistic regression. The results found the prevalence of stunting in Indonesia in 2014 was 36.6%. The stunting prevalence is higher in toddlers of married mothers of adolescents (42.4%) compared to mothers of married mature (35%). The stunting prevalence was also higher in children under five years from adolescent pregnant women (44.4%) compared to mothers who were of sufficient age (35.6%). Teenage pregnancy is associated with the incidence of stunting. A married teenage woman is 1.2 times at risk, and a woman who is less than 20 years pregnant is 1.3 times at risk of having a stunting toddler. Teenage pregnancy increases the prevalence of stunting. Cross-sectoral integrated interventioans are needed to prevent adolescent pregnancy. It is required to decrease the prevalence of stunting. The various risks that occur in teenage pregnancy are the basis for the importance of pregnancy prevention efforts in this age group by involving the related sectors.